Analysis of teacher-students interactions in a written language learning setting - Bazán Ramírez, Aldo (2002)
Teacher-student interactions in a reading and writing learning setting in first grade of elementary school, were analyzed taking the teaching method into consideration. Among the groups of children whom were taught with strategies derived from interbehavioral psychology, a larger number of interactions in qualitatively more complex levels are observed, this means that in these groups we observe interactions with non-apparent properties of the objects, and relations with extra-situational referents.$esides, in the mentioned groups we observed that interactions initiated by group teachers were followed with a very high probability by students' behaviors,in the same complexity le veis where the teachers' behaviors appeared.